All About the Ligamentum Teres: From Biomechanical Role to Surgical Reconstruction. Issue 8 (15th April 2020) - Rosinsky, Philip J.; Shapira, Jacob; Lall, Ajay C.; Domb, Benjamin G.
Abstract : Intriguing anatomists and surgeons for centuries, the exact function and biomechanical significance of the ligamentum teres (LT) remains incompletely understood. The LT, also described as the ligamentum femoris capitis, is an intra-articular extrasynovial ligament extending from the cotyloid fossa of the acetabulum to the fovea on the femoral head. Some studies have described it as a vestigial structure in the adult hip. More recent biomechanical studies, however, along with histological and anatomical studies, have suggested the LT to have an important function in proprioception, nociception, and as a secondary stabilizer of the hip joint. The advent and increased utilization of hip arthroscopy to treat hip pathology over the past two decades has ignited a renewed interest in the role of the LT, as well as techniques and indications for management of pathology. In the constellation of intra-articular pain generators of the hip, LT injuries have historically been difficult to diagnose through physical examination or advanced imaging. Numerous classification systems have been proposed based on arthroscopic appearance, and for most cases, conservative management is adequate. In patients undergoing hip arthroscopy, LT débridement usually suffices, although in cases of persistent pain and severe instability, reconstruction of the ligament may be indicated. Multiple methods for reconstruction have been described, with the greatest variation in the method of acetabular fixation of the graft. Future research should focus on clarifying the role of the LT, appropriate surgical indications for reconstruction, and optimization of graft fixation within the acetabulum.